Severe Eosinophilic Meningoencephalitis Secondary to Suspected Neuroangiostrongyliasis with a Good Clinical Outcome - Fabian Chiong; Andrew R. Lloyd; Jeffrey J. Post (Case Reports in Infectious Diseases)
Angiostrongylus cantonensis has caused sporadic cases of eosinophilic meningoencephalitis in Sydney, Australia. We describe a 36-year-old man who presented subacutely with fevers, reduced level of consciousness, confusion, ophthalmoplegia, and urinary incontinence. He was diagnosed with severe eosinophilic meningoencephalitis secondary to suspected Angiostrongylus cantonensis based on clinical, serological, and radiological findings. The patient was treated with albendazole and prednisolone with full neurological recovery. Management of neuroangiostrongyliasis with anthelminthic is controversial as it is thought to cause worsened outcomes through inciting an inflammatory response as a result of parasite killing. We managed to successfully treat our patient using albendazole and prednisolone and achieved a good outcome.